Male Perspective on Women in Contemporary Indonesian Islamic Literature - Wajiran, Wajiran (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
This paper aims at discussing the image of women in contemporary Indonesian Islamic literature after the ‘Indonesian Reformation’ in 1998. In contrast to the previous era, the images of women in this period are presented differently by male writers. Women are depicted more moderate and progressive. This paper applies the method of sociology of literature whereby literature is regarded as a reflection of its society. It employs content analysis of the text to see how Javanese Muslim women are depicted and how the depiction reflects the society. Two novels discussed in this paper are Cinta Suci Zahrana by Habiburrahman El Shirazy and Perempuan Badai by Mustofa W. Hasyim. The results show that these novels raise various issues of Muslim women in contemporary Indonesia. They show that there is a development in presenting the image of Muslim women in Indonesia. There is a development of thoughts, especially about the social status of women. The changes include the level of education, determination of spouse and freedom to participate in public spheres. The level of education obtained by the main characters is an essential milestone in changing women’s position in Indonesian Muslim society. Women are not just an object, but they should be the subject in the life of the Muslim community.